Probiotic Bacteria and Their Cell Walls Induce Th1-Type Immunity Against Salmonella Typhimurium Challenge - Lemme-Dumit, José María; Cazorla, Silvia Inés; Perdigón, Gabriela Del Valle; Maldonado-Galdeano, Carolina (Frontiers in Immunology, 2021)
Probiotics have been associated with a variety of health benefits. They can act as adjuvant to enhance specific immune response. Bacterial cell wall (CW) molecules are key structures that interact with host receptors promoting probiotic effects. The adjuvant capacity underlying this sub-cellular fraction purified from Lactobacillus casei CRL431 and L. paracasei CNCMI-1518 remains to be characterized. We interrogated the molecular and cellular events after oral feeding with probiotic-derived CW in addition to heat-inactivated Salmonella Typhimurium and their subsequent protective capacity against S. Typhimurium challenge. Intact probiotic bacteria were orally administered for comparison. We find that previous oral feeding with probiotics or their sub-cellular fraction reduce bacterial burden in spleen and liver after Salmonella challenge. Antibody responses after pathogen challenge were negligible, characterized by not major changes in the antibody-mediated phagocytic activity, and in the levels of total and Salmonella-specific intestinal sIgA and serum IgG, respectively. Conversely, the beneficial effect of probiotic-derived CW after S. Typhimurium challenge were ascribed to a Th1-type cell-mediated immunity which was characterized by augmentation of the delayed-type hypersensitivity response. The cell-mediated immunity associated with the oral feeding with probiotic-derived CW was accompanied with a Th1-cell polarizing cytokines, distinguished by increase IFN-/IL-4 ratio. Similar results were observed with the intact probiotics. Our study identified molecular events associated with the oral administration of sub-cellular structures derived from probiotics and their adjuvant capacity to exert immune modulatory function.